Evaluación biológica de los lodos residuales usando frijol (phaseolus vulgaris) y haba (vicia faba) - Colín Cruz, Arturo; Mulia Muñoz, Emma; Gomeztagle Hidalgo, María Mercedes; Moreno Alcántara, Jaime (CIENCIA ergo-sum; Vol. 1 Núm. 1 (1994): CIENCIA ergo-sum (marzo-junio 1994), 2017)
-